Deficiency of G9a Inhibits Cell Proliferation and Activates Autophagy via Transcriptionally Regulating c-Myc Expression in Glioblastoma - Ke, Xiao Xue; Zhang, Rui; Zhong, Xi; Zhang, Lei; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2020)
Glioblastoma is an aggressive and difficult to treat cancer. Recent data have emerged implicating that histone modification level may play a crucial role in glioma genesis. The histone lysine methyltransferase G9a is mainly responsible for the mono- and di-methylation of histone H3 lysine 9 (H3K9), whose overexpression is associated with a more aggressive phenotype in cancer. However, the detailed correlations between G9a and glioblastoma genesis remain to be further elucidated. Here, we show that G9a is essential for glioblastoma carcinogenesis and reveal a probable mechanism of it in cell proliferation control. We found that G9a was highly expressed in glioblastoma cells, and knockdown or inhibition of G9a significantly repressed cell proliferation and tumorigenesis ability both in vitro and in vivo. Besides, knockdown or inhibition of G9a led to a cell cycle arrest in G2 phase, as well as decreased the expression of CDK1, CDK2, Cyclin A2, and Cyclin B1, while it induced the activation of autophagy. Further investigation showed that G9a deficiency induced cell proliferation suppression, and activation of autophagy was rescued by overexpression of the full-length c-Myc. Chromatin immunoprecipitation (ChIP) assay showed that G9a was enriched on the −2267 to −1949 region of the c-Myc promoter in LN-229 cells and the −1949 to −1630 region of the c-Myc promoter in U-87 MG cells. Dual-luciferase reporter assay showed that c-Myc promoter activity was significantly reduced after knockdown or inhibition of G9a. Our study shows that G9a controls glioblastoma cell proliferation by transcriptionally modulating oncogene c-Myc and provides insight into the capabilities of G9a working as a potential therapeutic target in glioblastoma.